Promoting individual spirituality to enhance employee readiness to change in Islamic institutions - Mardhatillah, Amy Mardhatillah; Abdul Rahman, Shukran; Ismail, Khamsiah (2015)
Topic on readiness to change: the willingness of employees to accept change initiative has been discusses in organizational and management study. This study investigates the role of individual spirituality in predicting employee readiness to change in Islamic intitution. The present study also examined the role of job satisfaction and organizational commitment in mediating the relationship between individual spirituality and employee readiness to change.428 random sampling of International Islamic University Malaysia (IIUM) staff consisting 214 academic staff and 214 non academic staff were participated in this study trough the cross sectional design data collection. PLS SEM analysis was used to answer the research questions. Result indicated that individual spirituality significantly predicts employee readiness to change. Individual spirituality significantly related with job satisfaction and organizational commitment, however only organizational commitment significantly mediate the relationship between individual spirituality and employee readiness to change. Further analysis on the relationship between individual spirituality with three types of employee readiness namely; affective readiness, behavioral readiness and cognitive readiness found that individual spirituality significantly predicts behavioral readiness. Findings in this study can be used to enhance employee readiness in IIUM as well as a general framework in preparing intervention for enhancing employee readiness to change in Islamic institution.